Estimating Company Value of PT. Sarana Menara Nusantara Tbk - Setianto, Aryudho Mahardi; Noveria, Ana (Journal of Business and Management, 2012)
This paper examines valuation process of PT Sarana Menara Nusantara (SMN) Tbk, a company in tower telecommunication industry. SMN currently is the market leader of its sector, and on its high growth stage. The valuation was conducted using three different methods, which are asset-based valuation, market approach, and discounted cash flow with three different scenarios, which are most likely, pessimistic, and optimistic. The result of this research will be used as suggestion to the companyÃ¢â‚¬â„¢s management board to increase its value and maintain its growth. Furthermore, the fair stock value per share also calculated in this study, and will be compared to the current market value of the stock, because SMN is a public listed company. The result shows that the company value for 1 January 2012 ranged from Rp 8,568,330,000,000 Ã¢â‚¬â€œ Rp 22,035,565,508,695 after calculated using those three methods, and the fair stock value per share were below the current market value.Purpose: This research focuses on valuating PT Sarana Menara Nusantara (SMN). Then this research will be continued to find recommendation about strategies and actions that can be implemented by the company to maximize its company value and increase shareholderÃ¢â‚¬â„¢s wealth.Design/methodology/approach: Methods that used in this research were asset-based value, Price to Earning Ratio, and mainly Discounted Cash Flow, with using weighted average cost of capital as the discount rate. Quantitative data was used and it is taken from audited financial report of the company.Findings: The result shows that the company value for 1 January 2012 ranged from Rp 8,568,330,000,000 Ã¢â‚¬â€œ Rp 22,035,565,508,695 after calculated using those three methods. The fair stock value per share were below the current market value. The high market price is caused by market perception, perceiving that the company is now on a high growth stage.Research limitations/implications (if applicable): This research was conducted by collecting and analyszing the financial report of PT Sarana Menara Nusantara (SMN) in the period of 2009-2011. The research focuses on valuing the firm and estimating the value of company stock per share.Originality/value: The paper valued a public listed company, andÃ‚Â Valuation;Kewords: Corporate Finance; Discounted Cash Flow; WACC; P/E Ratio; Asset-based value, Projection; tower industry; public listed companyCategory: Finance;